Resurgent Bharat and other issues: an anthology of essays - Bhattacharjee,Jay (Gurugram Garuda, 2021)
Resurgent Bharat and Other Issues: An Anthology of Essays by Jay Bhattacharjee is a collection of essays published over a period of more than two decades in different newspapers like The Pioneer, The New Indian Express, The Business Standard; magazines like India Defence Review, besides various online portals, including Swarajya and NITI Central. These essays cover a wide-ranging of topics including India$1 (Bs civilisation and culture, politics, issues related to national security and neglect of the Indian soldiers by the establishment, corporate governance; and, humour and satire. The essays, written with historical references and parallels and unwaveringly sticking to the nationalistic perspective, without mincing words, are a wake-up call to all those wishing to see India back at the top, with its ancient glory and heritage restored. (3z(BThere are cogent reasons for putting together the diverse writings that this book contains. The first one is that our country that happens to be one of this planet$1 (Bs oldest surviving civilisations is also a young political entity, compared to many other nation-states in the world$1! = (BThere are grave existential threats that it confronts. Minimising these dangers would amount to burying our collective heads under the sand,(3y (Bsays the author.s
Keywords: Political -- Indian